2015
DOI: 10.1016/j.abb.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The busulfan metabolite EdAG irreversibly glutathionylates glutaredoxins

Abstract: The DNA alkylating agent busulfan is used to ‘precondition’ patients with leukemia, lymphomas and other hematological disorders prior to hematopoietic stem cell transplants. Busulfan is metabolized via conjugation with glutathione (GSH) followed by intramolecular rearrangement to the GSH analog γ–glutamyl-dehydroalanyl-glycine (EdAG). EdAG contains the electrophilic dehydroalanine, which is expected to react with protein nucleophiles, particularly proteins with GSH binding sites such as glutaredoxins (Grx’s). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Trx activity was determined using the method of Holmgren and Björnstedt with rat TrxR1 as a Trx reductase, the activity was presented in terms of µmol of NADPH oxidized/min/mg protein [27]. GR activity was measured by the method of Carlberg and Mannervik with oxidized glutathione as a substrate [28], and Grx activity was determined according to the method of Scian and Atkins with 2-hydroxyethyl disulfide as a model substrate [29]. Both GR and Grx activities were presented in terms of nmol of NADPH oxidized/min/mg protein.…”
Section: Methodsmentioning
confidence: 99%
“…Trx activity was determined using the method of Holmgren and Björnstedt with rat TrxR1 as a Trx reductase, the activity was presented in terms of µmol of NADPH oxidized/min/mg protein [27]. GR activity was measured by the method of Carlberg and Mannervik with oxidized glutathione as a substrate [28], and Grx activity was determined according to the method of Scian and Atkins with 2-hydroxyethyl disulfide as a model substrate [29]. Both GR and Grx activities were presented in terms of nmol of NADPH oxidized/min/mg protein.…”
Section: Methodsmentioning
confidence: 99%
“…The work of Younis et al . [24] found that EdAG binds to GST A1, the major GST isoform responsible for Bu conjugation; per contra, Scian et al [23] demonstrated that EdAG does not bind to the GSH binding site on GST A1, but does irreversibly bind to a cysteine residue in the GSH binding pocket of glutaredoxin, resulting in a catalytically inactive protein [23]. …”
Section: Bu Metabolismmentioning
confidence: 99%
“…EdAG has been shown to irreversibly glutathionylate and inhibit Grx's which play a critical role in the glutathionylation and deglutathionylation of many proteins. Grx's are important for many cellular regulatory processes [1] . Many other redoxins that contain active site cys residues in GSH binding sites, or other proteins with nucleophilic cys residues, may be targets for EdAG as well.…”
Section: Datamentioning
confidence: 99%
“… This article describes data related to a research article titled “The Busulfan Metabolite EdAG Irreversibly Glutathionylates Glutaredoxins” [1] . EdAG is an electrophilic GSH analog formed in vivo from busulfan, which is used in hematopoietic stem cell transplants.…”
mentioning
confidence: 99%